Executive Director's Message - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2015)
Many of you may ask the question, “Why should I join ORNAC? The Operating Room Nurses Association of Canada (ORNAC) is a not-for-profit association and the national voice for Perioperative Registered Nurses across Canada. ORNAC strives to advance the profession of Perioperative Registered Nursing and to form strategic partnerships that support patient safety. ORNAC acts in the interests of those engaged in the profession as well as in the interest of the public. By joining ORNAC you automatically become a member of your Provincial Council (formerly the provincial perioperative nursing associations) which provides you with access to local networking.